Atividades antinociceptiva e anti-inflamatória de uma fração rica em heterogalactana sulfatada extraída da alga Codium isthmocladum (Vickers 1905) - Cordeiro, Sara Lima (2013)
Sulfated polysaccharides comprise a complex group of macromolecules with a range of several biological activities, including antiviral activity, anticoagulant, antiproliferative, antiherpética, antitumor, anti-inflammatory and antioxidant. These anionic polymers are widely distributed in tissues of vertebrates, invertebrates and algae. Seaweeds are the most abundant sources of sulfated polysaccharides in nature. The green algal sulfated polysaccharides are homo or heteropolysaccharides comprised of galactose, glucose, arabinose and/or glucuronic acid. They are described as anticoagulant, anti-inflammatory, antiviral, anti-angiogenic, antitumor compounds. However, there are few studies about elucidation and evaluation of biological/pharmacological effects of sulfated polysaccharides obtained from green algae, for example, there is only one paper reporting the antinociceptive activity of sulfated polysaccharides of these algae. Therefore this study aimed to obtain sulfated polysaccharides of green seaweed Codium isthmocladum and evaluates them as potential antinociceptive agents. Thus, in this study, the total extract of polysaccharides of green alga C. isthmocladum was obtained by proteolytic digestion, followed by fractionation resulting in five fractions (F0.3, F0.5, F0.7, F0.9 and F1.2) by sequential precipitation with acetone. Using the test of abdominal contractions we observed that the fraction F0.9 was the most potent antinociceptive aompound. F0.9 consists mainly of a sulfated heterogalactana. More specific tests showed that Fo.9 effect is dose and time dependent, reaching a maximum at 90 after administration (10 mg / kg of animal). F0.9 is associated with TRPV1 and TRPA1 receptors and inhibits painful sensation in animals. Furthermore, F0.9 inhibits the migration of lymphocytes induced peritonitis test. On the other hand, stimulates the release of NO and TNF-α. These results suggest that F0.9 has the potential to be used as a source of sulfated galactan antinociceptive and anti-inflammatory